In-vitro, In-vivo, and In-silico Studies of Insulinotropic Activity and Cytotoxicity of Mahagony Seed Extracts and Its Nanophytosome - Zikri Hamidi; Rita Kartika Sari; Yanico Hadi Prayogo; Wasrin Syafii; Adinda Zahra Marissa Kasmi; Bayu Febram Prasetyo; Eva Harlina; Setyanto Tri Wahyudi (Communications in Science and Technology, 2025)
This present study set out with the objective of evaluating the effect of ethanol–water solvent composition on extraction yield, insulinotropic activity (IA), cytotoxicity, and phytochemical profile (PP) of mahogany (Swietenia mahagoni) seed (MS) extracts. It also sought to study in silico and encapsulate the best extract, and to assay the antidiabetic of the extract and its nanophytosome. The extraction of MSs was achieved through the utilization of ethanol, ethanol–water (1:1), and water through ultrasound–assisted extraction. The extracts of IA and cytotoxicity were assayed in vitro using BRIN–BD11 cell lines and analyzed using LC-MS. The most effective extract was identified for its active compounds using molecular docking, encapsulation, characterization, and testing for its antidiabetic properties in vivo. The highest yield was observed in the water extract (MW), followed by the ethanol–water extract (MEW) and the ethanol extract (ME). MEW and MW demonstrated low level of cytotoxicity, with MEW exhibiting the highest level of IA. An in silico study identified four key antidiabetic compounds through the IA mechanism. The study demonstrated that MEW and its nanophytosome (250 mg/kg mouse weight) effectively reduced blood glucose level, and enhanced both erythrocyte function, and insulin secretion. This finding provides a new perspective in the development of natural-based antidiabetic agents through the nanophytosome formulation of mahogany seed extract.